2018
DOI: 10.1097/ede.0000000000000766
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Effect of Preventable Treatment Discontinuation on Health Outcomes

Abstract: Inverse-probability of censoring weighted estimation can be used to estimate the effect of potentially preventable treatment discontinuation in populations where treatment can be stopped for both medical and nonmedical reasons. Estimates from such approaches may represent an upper bound of what would be achievable by an adherence improvement intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In a similar study on the effect of preventable treatment discontinuation, medically indicated treatment discontinuation was not considered "preventable." 14 Because contraindications for rotavirus vaccination are very rare, 42,43 the bias resulting from the occurrence of these events during follow-up is likely small. Second, our study was conducted under the assumption of no interference (i.e., the potential outcomes of one individual are assumed to be unaffected by the exposure of other individuals).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar study on the effect of preventable treatment discontinuation, medically indicated treatment discontinuation was not considered "preventable." 14 Because contraindications for rotavirus vaccination are very rare, 42,43 the bias resulting from the occurrence of these events during follow-up is likely small. Second, our study was conducted under the assumption of no interference (i.e., the potential outcomes of one individual are assumed to be unaffected by the exposure of other individuals).…”
Section: Discussionmentioning
confidence: 99%
“…10 The general approach has been used to study the effect of dynamic treatment regimens, [11][12][13] and to study the population attributable effect of preventing treatment discontinuation. 14 Here, we apply the approach in the context of a study of various RV schedules for the prevention of acute gastroenteritis -related hospitalization and emergency department (ED) visits during early childhood. The effectiveness of full-and partial-series completion with the two-dose monovalent RV, Rotarix (RV1; GlaxoSmithKline Biologicals, Rixensart, Belgium), and the three-dose pentavalent RV, RotaTeq (RV5; Merck & Co., Inc., Whitehouse Station, New Jersey, USA), have been well-established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing availability of RWD is further enhanced by the growing sophistication of epidemiologic and statistical methods, such as causal inference. [15][16][17][18][19][20][21] TARGET-NEURO was developed to address the current gaps in research on patients with chronic neurological diseases and capitalize upon the potential medical and health insights that data in EHR systems can provide. The overarching goal of TARGET-NEURO is to characterize the natural history of patients with chronic neurological diseases (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It directly reduces PTH levels with an additional resultant effect of decreasing serum calcium and phosphorus levels [12, 13]. As with most chronically administered medications, the putative benefits of cinacalcet therapy are thought to manifest when patients are taking it consistently as prescribed, and consequently, the benefits of cinacalcet may not be fully realized when not remaining on therapy [14].…”
Section: Introductionmentioning
confidence: 99%